MENINGKATKAN KEMAMPUAN BERTANYA SISWA KELAS IV SD NEGERI 1 DUFA-DUFA KOTATERNATE MELALUI MODEL PEMBELAJARAN PROBLEM POSING - Sahil, Jailan; Faisal, M. (BIOEDUKASI, 2012)
Problem Posing constituting learning model that is adapted with competence student, and in its learning process build cognitives structure student and gets to motivate student for over thinks critical and creative deep problem proffering (ask). This research intent to know ability step-up asks on student brazes IV. SDN 1 Dufa-Dufa Ternates City school year 2009-2010.In this research method which is utilized is observational action braze (Classroom Action Research)utilizing path / planning cycle, action performing, watch, and reflection. This observational subject is student braze IV. SDN 1 Dufa-Dufa Ternates City school year 2009-2010 total one 25 person. This research  consisting  of  2  cycles.  Acquired  data  by  observing  (observation)  while  done  by  action  and academic achievement test result document individual each cycle final. The analyze data is done by use of qualitative analyze models and  triangulation.Result observationaling to point out that ability asks on student brazes IV. SDN 1 Dufa-Dufa Ternates City school year 2009-2010 experiences step-up. It also being followed at the height student studying  result.  After  been  done  action  on  cycle  I,  students  learned  result  which  reach  Minimal thoroughness Criterion point (KKM) as big as 52% and student activity in perform learning as big as 65 % of all total students. On cycle II, result studies student that reaches to assess  thoroughness Criterion (KKM) as big as 100% and student activity in perform learning as big as 93 % of all  students. Keywords:  Ability asks, problem possings learning model